Thickness and nanomechanical properties of protective layer formed by TiF4 varnish on enamel after erosion - Maria Isabel Dantas de MEDEIROS; Hugo Lemes CARLO; Rogério LACERDA-SANTOS; Bruno Alessandro Guedes de LIMA; Frederico Barbosa de SOUZA; Jonas Almeida RODRIGUES; Fabiola Galbiatti de CARVALHO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The layer formed by fluoride compounds on tooth surface is important to protect the underlying enamel from erosion. However, there is no investigation into the properties of protective layer formed by NaF and TiF4 varnishes on eroded enamel. This study aimed to evaluate the thickness, topography, nanohardness, and elastic modulus of the protective layer formed by NaF and TiF4 varnishes on enamel after erosion using nanoindentation and atomic force microscopy (AFM). Human enamel specimens were sorted into control, NaF, and TiF4 varnish groups (n = 10). The initial nanohardness and elastic modulus values were obtained and varnishes were applied to the enamel and submitted to erosive challenge (10 cycles: 5 s cola drink/5 s artificial saliva). Thereafter, nanohardness and elastic modulus were measured. Both topography and thickness were evaluated by AFM. The data were subjected to ANOVA, Tukey's test and Student's t test (α = 0.05). After erosion, TiF4 showed a thicker protective layer compared to the NaF group and nanohardness and elastic modulus values were significantly lower than those of the control group. It was not possible to measure nanohardness and elastic modulus in the NaF group due to the thin protective layer formed. AFM showed globular deposits, which completely covered the eroded surface in the TiF4 group. After erosive challenge, the protective layer formed by TiF4 varnish showed significant properties and it was thicker than the layer formed by NaF varnish.